Hedging effectiveness of Malaysian derivative markets under different asset classes - Salami, Monsurat Ayojimi; Haron, Razali (2019)
This presentation discusses hedging effectiveness of Malaysian derivative markets under different asset classes. The finding concludes that there exist interaction between underlying and derivative markets in Malaysia.